1992
DOI: 10.1088/0963-0252/1/1/007
|View full text |Cite
|
Sign up to set email alerts
|

The role of substrate temperature and bias in the plasma deposition from tetramethylsilane

Abstract: Thin transparent polymeric films have been deposited from lowpressure argonltetramethylsilane radio-frequency glow discharges at controlled substrate bias and temperature. The effect of positive ion bombardment and substrate temperature on both film growth rate and chemical composition has been studied. An account of the post-discharge fast oxidation of films exposed to oxygen is also given. A general deposition mechanism% proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 24 publications
(9 reference statements)
3
20
0
1
Order By: Relevance
“…[9,24] We note that the analogous Arrhenius plots, exhibiting E a < 0, are reported for a-SiC:H films grown by PCVD from various organosilicon precursors. [25,26] The kinetics data presented in Figure 2 reveal distinct differences in the mechanisms of RHP-CVD and PCVD, which seem to be mainly due to a much lower concentration of active species inducing the former process (i.e., atomic hydrogen) and resulting in a lower content of the produced film-forming precursors than in the latter process. This is consistent with the smaller value of a-SiC:H film growth rate, determined for RHP-CVD, r d ¼ 6.0 AE 0.9 nm min À1 , with respect to that of PCVD, r d ¼ 13 À 122 nm min À1 (Fig.…”
Section: Effect Of Thermal Activationmentioning
confidence: 99%
“…[9,24] We note that the analogous Arrhenius plots, exhibiting E a < 0, are reported for a-SiC:H films grown by PCVD from various organosilicon precursors. [25,26] The kinetics data presented in Figure 2 reveal distinct differences in the mechanisms of RHP-CVD and PCVD, which seem to be mainly due to a much lower concentration of active species inducing the former process (i.e., atomic hydrogen) and resulting in a lower content of the produced film-forming precursors than in the latter process. This is consistent with the smaller value of a-SiC:H film growth rate, determined for RHP-CVD, r d ¼ 6.0 AE 0.9 nm min À1 , with respect to that of PCVD, r d ¼ 13 À 122 nm min À1 (Fig.…”
Section: Effect Of Thermal Activationmentioning
confidence: 99%
“…Moreover, due to its molecular structure, it is possible to obtain materials with compositions ranging from silicon carbide to silicon oxide. [11,12] Recently, the preparation of low-k SiO x C y H z thin films by PECVD from TMS mixtures has been reported by some authors. [13] Compared to other precursors, the plasma chemistry of TMS is not completely understood, particularly in oxygen/ TMS mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the temperature effect, the increase in the Si/C ratio when the temperature is increased from 453 to 853 K has already been discussed by Favia et al [32] They suggested that any thermal activation lowers the content of H atoms and CH x , leading to a larger cross-linking and to an increase in the Si/C ratio. Concerning the ion bombardment effect, Si/C decreases inversely with the maximum ion energy.…”
Section: Discussionmentioning
confidence: 86%